Age‐Friendly Initiatives, Social Inequalities, and Spatial Justice. (11th October 2018) - Greenfield, Emily A.
Abstract: Discourse on communities and aging traditionally has focused on the availability, accessibility, and quality of local services to support older adults in need of assistance. More recently, however, a growing worldwide "age‐friendly" movement has pushed the conceptualization of community supports for an aging society beyond service provision. The term "age friendly" is used in considering how various aspects of a community facilitate or impede the health and well‐being of individuals as they experience long lives . Frameworks on age friendliness include attention to health and community services for older adults but also encompass other aspects of communities, such as the physical design of outdoor spaces and buildings, the diversity of mobility options for drivers and nondrivers alike, and the availability of safe, affordable, and various types of housing. Age‐friendly frameworks also highlight how the very social fabric of a community can influence older residents' quality of life. Over the past decade, a growing number of cities and communities have launched age‐friendly initiatives as organized and comprehensive efforts to make localities better for residents as they age. This essay begins to explore how AFIs can address social inequalities in health and aging. It concludes by describing how embedding a spatial justice lens within age‐friendly efforts could help AFIs realize more fully the changes that they seek to create at the local, national, and global levels .